Reviewing the Three-Sentence Story Writing Training Program (Tatika) in Raising Literacy Interests of Middle School Students - Nida Amalia Manggala; Yaya Sunarya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The low literacy rate of Indonesians was the background for the government to launch the School Literacy Movement (GLS) program in 2016 with the hope of improving students' literacy culture in schools. This study aims to determine the impact of one of the School Literacy Movement programs at SMPN 39 Bandung, namely the Three-Sentence Story Writing Training (Tatika) on the reading and writing interests of SMPN 39 Bandung students. The method used in this study is a qualitative method. Data collection techniques used were interviews with the principal and teachers as the implementing committee for the Tatika program, distributing questionnaires, and field observations. Based on the results of the study, with the holding of the